Contribution of the Fenton reaction to the degradation of carbon nanotubes by enzymes - Takahashi, Seira; Taguchi, Fumiko; Hori, Katsutoshi (Frontiers in Environmental Science, 2023)
The widespread use of carbon nanotubes (CNTs) has raised concerns about the human health and ecological effects of CNTs released into the environment. Bacteria play an important role in bioremediation and waste treatment, and their enzymes are mostly responsible for the degradation of contaminants. However, there are still only a few reports about the bacterial degradation of CNTs, and evidence showing the involvement of bacterial enzymes in CNT degradation with their mechanisms has never been reported. The purpose of this study is to clarify whether CNTs can be degraded by bacterial enzymes. In this study, the degradation of oxidized (carboxylated) single-walled CNTs (O-SWCNTs) by mt2DyP, a dye-decolorizing peroxidase of Pseudomonas putida mt-2, a common soil bacterium, was investigated. After incubation of O-SWCNTs with recombinant mt2DyP and its substrate H2O2 for 30 d, the optical absorbance and Raman spectra revealed the degradation of O-SWCNTs. However, inactivation of the enzyme was observed within 60 min of the start of incubation, suggesting that the degradation of O-SWCNTs occurred nonenzymatically. The inactivation of mt2DyP was accompanied by the release of iron, the active center metal, and degradation of O-SWCNTs was significantly inhibited in the presence of diethylenetriamine pentaacetic acid, a chelating agent, indicating that O-SWCNTs were degraded by the Fenton reaction with iron released from mt2DyP and H2O2. The same phenomenon was observed with P450, which is also a heme enzyme. Furthermore, we investigated the contribution of the Fenton reaction to the O-SWCNT degradation by horseradish peroxidase (HRP), which was reported to enzymatically and rapidly degrade O-SWCNTs. Our results revealed that the degradation of O-SWCNTs in the presence of HRP is also mainly due to the Fenton reaction, with negligible enzymatic degradation. This contradicts the report showing enzymatic degradation of O-SWCNTs by HRP but supports the subsequent report quantitatively showing very slow transformation of O-SWCNTs by HRP. The current results emphasize that the Fenton reaction, which has received little attention in CNT degradation by heme enzymes, must be taken into consideration and will contribute to the development of a simple disposal method for CNTs, utilizing the Fenton reaction with bacteria/bacterial enzymes and H2O2.